Altered regional cortical thickness and subcortical volume in women with primary dysmenorrhoea. (29th July 2015) - Liu, P.; Yang, J.; Wang, G.; Liu, Y.; Liu, X.; Jin, L.; Liang, F.; Qin, W.; Calhoun, V.D.
Abstract: Background: There is emerging evidence that primary dysmenorrhoea (PDM) is associated with altered brain function and structure. However, few studies have investigated changes in regional cortical thickness and subcortical volumes in PDM patients. The purpose of this study was to characterize differences in both cortical thickness and subcortical volumes between PDM patients and healthy controls (HCs). Methods: T1‐weighted magnetic resonance images were obtained from 44 PDM patients and 32 HCs matched for age and handedness. Cortical thickness was compared in multiple locations across the continuous cortical surface, and subcortical volumes were compared on a structure‐by‐structure basis. Correlation analysis was then used to evaluate relationships between the clinical symptoms and abnormal brain structure in PDM. Results: PDM patients had significantly increased cortical thickness in the orbitofrontal cortex (OFC), insula (IN), primary/secondary sensory area (SI/SII), superior temporal cortex (STC), precuneus (pCUN) and posterior cingulate cortex (PCC). Meanwhile, significantly decreased subcortical volumes of the caudate, thalamus and amygdala were found in PDM patients. Moreover, there were significant positive correlations between the PDM‐related duration and the OFC, SFC, STC and IN. The MPQ scores were positively correlated with the pCUN. Conclusions: These findings provide further evidence for grey matter changes in patients with PDM, and in addition, the results support relationships between the structural abnormalities and their role in symptom production. All these results are likely to be potential valuable to provide us with direct information about the neural basis of PDM.